2016
DOI: 10.1111/socf.12269
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Organizational Commitment: Adding Frames to Greedy Institution Theory

Abstract: How do organizations that make significant physical, emotional, and intellectual demands foster commitment and loyalty from voluntary participants? Greedy institution theory (Coser 1974) answers this question by identifying structural elements that foster participants' undivided commitment to "greedy" groups, those in which participants' involvement interferes with and takes precedence over their involvement in other social spheres. In this article, I argue for the expansion of greedy institution theory to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…This innate understanding is especially conspicuous in career mentoring (as is also noted in the Getting Up and Dropping Down section), since career development initiatives derived from white-collar assumptions fail to meet the needs of blue-collar workers, who make sense of career and success in unique ways (Lucas & Buzzanell, 2004). Other implications of similar interventions were also reported: A program preparing low-income students of color for elite schools elicited students’ undivided loyalty to the organization at the expense of other relationships (Cox, 2016). Ramarajan and Reid (2020) reported that low-income students were socialized into upper class norms in an urban charter high school, though the “socialization agents” (i.e., White, upper class tutors tasked with integrating new students into the school) experienced and navigated tension stemming from the race and class inequalities.…”
Section: Getting Alongmentioning
confidence: 97%
“…This innate understanding is especially conspicuous in career mentoring (as is also noted in the Getting Up and Dropping Down section), since career development initiatives derived from white-collar assumptions fail to meet the needs of blue-collar workers, who make sense of career and success in unique ways (Lucas & Buzzanell, 2004). Other implications of similar interventions were also reported: A program preparing low-income students of color for elite schools elicited students’ undivided loyalty to the organization at the expense of other relationships (Cox, 2016). Ramarajan and Reid (2020) reported that low-income students were socialized into upper class norms in an urban charter high school, though the “socialization agents” (i.e., White, upper class tutors tasked with integrating new students into the school) experienced and navigated tension stemming from the race and class inequalities.…”
Section: Getting Alongmentioning
confidence: 97%
“…In the first identified main themes, implicit expectations for officers' private life, the data analysis indicated that the military officers perceived the need for themselves and their partner to prioritize and adapt their private life in accordance to the organisation's demands. In relation to theory regarding greedy organisations (Coser, 1974;Cox, 2016;Gerstel and Sarkisian, 2007), the adaptive behaviors described may be indicators of organisational greed that has manifested into the military officer's private life. This was exemplified by several participants' disclosure that the planning of family life, including if and when to have children, was done according to the organisation's demands.…”
Section: Discussionmentioning
confidence: 99%
“…How residential schools maintain order differs greatly. Some control through humiliation and mortification (Fear-Segal, 2007;Survival International, 2019;Truth and Reconciliation Commission of Canada, 2015), others rely on students' desire to be a part of the school and its legacy, while others project institutional transformational goals and pathways (Cox, 2016;Scott, 2011), whether realistic or not.…”
Section: Four Features Of Residential Schools As Total Institutionsmentioning
confidence: 99%